Multilayered Socialization Processes in Transgenerational Family Firms. (September 2019) - Bika, Zografia; Rosa, Peter; Karakas, Fahri
Building on an in-depth case study of a four-generational Scottish family firm, we generate a triple-layered model of socialization. Our findings go beyond the traditional focus on internal family socialization and value transmission and suggest that socialization involves three concentric layers unfolding over time, each with a distinct set of dimensions, values, challenges and processes: internal (transmitting knowledge within the family), interactive (resolving competing role demands through peer interactions), and experiential (interacting with both peer groups and malleable societal/economic frames). This novel theorization provides a promising framework for future research seeking to explain the complexities of socialization processes in transgenerational family firms.